Can Digital Finance Enhance Corporate Green Innovation Efficiency? - Wang, Jian; Gui, Na; Yan, Jiaying (Journal of Environmental Accounting and Management, 2026)
As the role and importance of financial support for the development of the real economy have significantly increased, whether digital finance can enhance corporate green innovation efficiency has become a hot topic of social concern. This paper uses data from A-share listed companies between 2011 and 2022, supported by the Digital Inclusive Finance Index developed by Peking University. A two-way fixed effects model, mediation effects model, and threshold effects model are employed to systematically examine the impact of digital finance on corporate green innovation efficiency. The results indicate that: (1) Digital finance can significantly improve corporate green innovation efficiency. This conclusion remains valid after a series of robustness checks; (2) Mechanism analysis reveals that digital platforms and transaction cost reduction are the primary channels of influence; Moreover, we identify a threshold effect: the positive impact diminishes with higher levels of digital finance coverage. (3) Heterogeneity tests indicate stronger effects among state-owned enterprises, high-tech firms, and low-pollution industries. These findings highlight the need for differentiated digital finance policies and green-oriented platform construction to support innovation efficiency under varying economic conditions.